Effectiveness Of E-Booklet Education In Improving Knowledge And Prevention Behavior Toward Preeclampsia Among Pregnant Women - Lestari, Kurniati Puji; Sari, Reni Titis Antika; Ningsih, Iis Sri; Wagiyo, Wagiyo (Jurnal Riset Kesehatan, 2025)
Preeclampsia is a dangerous condition for pregnant mothers that causes significant health problems worldwide. It is characterized by high blood pressure, with readings greater than 140/90 mmHg, occurring after 20 weeks of pregnancy. However, in reality, many pregnant mothers still do not know the methods to prevent preeclampsia. Studies show that the knowledge possessed by pregnant mothers influences their behavior; therefore, mothers with a lack of knowledge tend not to engage in preeclampsia prevention. This research aims to determine the relationship between the level of knowledge of pregnant mothers about preeclampsia and their behavior in preventing preeclampsia in the Padangsari Health Center work area. This study uses a quantitative method with a descriptive correlational design and a cross-sectional approach. The research was conducted in the Padangsari Health Center work area, Semarang City. The sample size consisted of 55 respondents, selected using a non-probability sampling technique, namely purposive sampling. Data analysis was performed using the Chi-Square test. The research instrument was a questionnaire measuring the level of knowledge about preeclampsia and preeclampsia prevention behavior, developed by the researcher and tested for validity and reliability. The results indicate a significant relationship between the level of knowledge and preeclampsia prevention behavior. The statistical test using the Chi-Square test yielded a significance value (sig-p = 0.000) < Î± (0.05), so Ho is rejected and Ha is accepted.